Unveiling Ethical Implications: AI Robot Accountability in Islamic Context - Hamsin, Muhammad Khaeruddin; Anggriawan, Rizaldy; Jiatrahman, Farisma (Jurnal Media Hukum, 2023)
The world is currently experiencing what is known as industry 4.0, a fusion of business and IT where robots and other forms of artificial intelligence are massively utilized. The fact that robots are now a regular part of people's lives raises novel liability issues. The research aims to address the questions whether artificial intelligence robots can be accepted as ethical and legal subjects in Islamic perspective. It also considers whether it is necessary to grant legal personality to robots and hold them liable for their decisions and conducts. The research is doctrinal legal research where the analysis was presented within the context of Islamic viewpoints in a descriptive-structured way. The result demonstrates that robots with artificial intelligence fall under the definition of jamadat. No matter how sophisticated, an artificial intelligence cannot have a biological vitality. Therefore, only humans have the potential to possess rights and be held liable for their actions. Robotic artificial intelligence systems lack the capacity to be regarded as responsible entities in this sense, to inflict legal sanctions on activities that are the result of algorithms, and to be held accountable for both civil and criminal offenses.